SUBSTRATES AND WATER AVAILABILITY ON THE EMERGENCE AND INITIAL GROWTH OF Alibertia sessilis Schum. SEEDLINGS - Mota, Leandro Henrique de Sousa; Scalon, Silvana de Paula Quintão; Heinz, Rafael; Dresch, Daiane Mugnol (Floresta, 2017)
The cultivation of native species in the Cerrado has encountered various problems, for instance, the slow growth and the lack of knowledge about the cultivation practices. In order to better use the available water resources and to produce quality seedlings, this study aimed to evaluate different substrates and water levels on the emergence and initial growth of Alibertia sessilis Schum. seedlings. The effects of the following substrates were evaluated: dystroferric Red Latosol (Oxisol), Oxisol +sand (1:1 v/v), Oxisol + sand + semi-decomposed poultry litter (1:1:0.5 v/v), Oxisol + sand 2 + semi-decomposed poultry litter (1:2:0.5 v/v) and Oxisol + commercial-substrate-CS (1:1 v/v) associated with the levels of irrigation of 25, 50, 75 and 100% of the water holding capacity in the substrate (WHC). The best results for emergence percentage, initial growth and quality of seedlings were observed in the substrates Oxisol + sand 2 + poultry litter (1:2:0,5) at 100% of WHC. There was no emergence at 25% of WHC. Keywords: Rubiaceae, marmelinho, fruit of the Cerrado. Resumo Substratos e disponibilidade hídrica na emergência e crescimento inicial de mudas de Alibertia sessilis Schum. O cultivo de espécies nativas no Cerrado tem esbarrado em vários problemas, entre eles, o crescimento lento e a carência de conhecimentos sobre as práticas culturais. A fim de melhor utilizar os recursos hídricos disponíveis e produzir mudas de qualidade, objetivou-se no presente trabalho avaliar diferentes substratos e níveis de água na emergência e no crescimento inicial das mudas Alibertia sessilis Schum. Foram avaliados os efeitos dos substratos Latossolo Vermelho distroférrico (LVd), LVd +areia (1:1 v/v), LVd + areia + cama de frango semidecomposta (1:1:0,5 v/v), LVd + areia 2 + cama de frango semidecomposta (1:2:0,5 v/v) e LVd + substrato comercial -SC (1:1 v/v) associados aos níveis de irrigação de 25, 50, 75 e 100% da capacidade de retenção de água no substrato (CRA). Os melhores resultados para porcentagem de emergência, crescimento inicial e qualidade das mudas foram observados nos substratos LVd + areia 2 + cama de frango (1:2:0,5) a 100% da CRA. Não houve emergência a 25% da CRA. Palavras-chave: Rubiaceae, marmelinho, frutífera do Cerrado.